The Lumber-Room Revisited - Bénabou, Marcel (2001)
Texto literario traducido al inglés por Ian Monk
Keywords: BÉNABOU, MARCEL; LITERATURA; FRANCIA; ÎLE-DE-FRANCE; VILLE DE PARIS; PARIS; PEREC, GEORGES